Slow lung clearance and limited translocation of four sizes of inhaled iridium nanoparticles. Issue 1 (December 2017) - Buckley, Alison; Warren, James; Hodgson, Alan; Marczylo, Tim; Ignatyev, Konstantin; Guo, Chang; Smith, Rachel
Abstract Background Concerns have been expressed that inhaled nanoparticles may behave differently to larger particles in terms of lung clearance and translocation, with potential implications for their toxicity. Studies undertaken to investigate this have typically involved limited post-exposure periods. There is a shortage of information on longer-term clearance and translocation patterns and their dependence on particle size, which this study aimed to address. Methods Rats were exposed (<3 h) nose-only to aerosols of spark-generated radioactive iridium-192 nanoparticles of four sizes: 10 nm, 15 nm, 35 nm and 75 nm (count median diameter) (aerosol mass concentrations 17, 140, 430, and 690 μg/m3, respectively). The content of iridium-192 in the whole animal, organs, tissues, and excreta was measured at various times post-exposure to ≥ 1 month. Limited toxicological investigations were undertaken for the 10 nm aerosol using bronchoalveolar lavage fluid. Elemental maps of tissue samples were produced using laser ablation inductively coupled plasma mass spectrometry and synchrotron micro-focus x-ray fluorescence. The chemical speciation of the iridium was explored using synchrotron micro focus x-ray near-edge absorption spectroscopy. Results Long-term lung retention half-times of several hundred days were found, which were not dependent on particle size. There was significant variation between individual animals. Analysis of bronchoalveolar lavage fluid for the 10 nm aerosol indicated a limited inflammatory response resolving within the first 7 days. Low levels of, particle size dependent, translocation to the kidney and liver were found (maximum 0.4% of the lung content). Any translocation to the brain was below the limits of detection (i.e. < 0.01% of the lung content). The kidney content increased to approximately 30 days and then remained broadly constant or decreased, whereas the content in the liver increased throughout the study. Laser ablation inductively coupled plasma mass spectrometry analysis indicated homogeneous iridium distribution in the liver and within the cortex in the kidney. Conclusions Slow lung clearance and a pattern of temporally increasing concentrations in key secondary target organs has been demonstrated for inhaled iridium aerosol particles < 100 nm, which may have implications for long-term toxicity, especially in the context of chronic exposures.